2020
DOI: 10.1108/prr-10-2019-0031
|View full text |Cite
|
Sign up to set email alerts
|

Impact of surface acting and deep acting techniques on teachers’ organizational commitment

Abstract: Purpose This paper aims to examine the relationship between surface acting (SA), deep acting (DA) and organizational commitment (OC). Design/methodology/approach Guided by affective events theory, the study adapted emotional labour scale and three components model to profile 373 teachers from 30 schools around Peninsular Malaysia. A list-based simple random sampling technique was used to select respondents. Structural equation modeling (SEM) was used to test hypotheses, and the proposed model was assessed th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
22
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(25 citation statements)
references
References 111 publications
2
22
0
1
Order By: Relevance
“…When teachers can exhibit emotional effort and transparency and transfer their negative emotions, they become more committed to the school. However, there are inconsistent findings in the literature on both teacher ( Isenbarger and Zembylas, 2006 ; Güler, 2018 ; Deliveli and Kıral, 2020 ; Ogunsola et al, 2020 ; Zheng et al, 2020 ) and other samples such as health employees ( Şenel and Aydoğan, 2020 ), hotel employees ( Büyükbeşe and Aslan, 2019 ), nurses ( Yang and Chang, 2008 ; Han S. S. et al, 2018 ), and IT workers ( Kim and Yang, 2018 ). While some of these studies suggest a positive association ( Isenbarger and Zembylas, 2006 ; Güler, 2018 ; Deliveli and Kıral, 2020 ; Şenel and Aydoğan, 2020 ), some others reveal that there is a negative relationship between EL and OC ( Han S. L. et al, 2018 ; Büyükbeşe and Aslan, 2019 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…When teachers can exhibit emotional effort and transparency and transfer their negative emotions, they become more committed to the school. However, there are inconsistent findings in the literature on both teacher ( Isenbarger and Zembylas, 2006 ; Güler, 2018 ; Deliveli and Kıral, 2020 ; Ogunsola et al, 2020 ; Zheng et al, 2020 ) and other samples such as health employees ( Şenel and Aydoğan, 2020 ), hotel employees ( Büyükbeşe and Aslan, 2019 ), nurses ( Yang and Chang, 2008 ; Han S. S. et al, 2018 ), and IT workers ( Kim and Yang, 2018 ). While some of these studies suggest a positive association ( Isenbarger and Zembylas, 2006 ; Güler, 2018 ; Deliveli and Kıral, 2020 ; Şenel and Aydoğan, 2020 ), some others reveal that there is a negative relationship between EL and OC ( Han S. L. et al, 2018 ; Büyükbeşe and Aslan, 2019 ).…”
Section: Resultsmentioning
confidence: 99%
“…While some of these studies suggest a positive association ( Isenbarger and Zembylas, 2006 ; Güler, 2018 ; Deliveli and Kıral, 2020 ; Şenel and Aydoğan, 2020 ), some others reveal that there is a negative relationship between EL and OC ( Han S. L. et al, 2018 ; Büyükbeşe and Aslan, 2019 ). Considering the relationships in terms of the dimensions, Zheng et al (2020) suggested that deep acting is positively associated with commitment and surface acting has a negative effect on it, while Ogunsola et al (2020) found that both surface and deep acting has a negative effect on OC. On the other hand, Yang and Chang (2008) indicated that surface acting has a significantly negative relationship with OC while deep acting does not have a significant effect on it.…”
Section: Resultsmentioning
confidence: 99%
“…In their study findings, Anas & Hamzah (2020) say that spiritual intelligence can make humans intellectually, emotionally, and spiritually complete. This is the same as the opinion of (e.g., Leonard & Biberman, 2007;Ogunsola et al, 2020;Opriş, 2015) that being smart is not only expressed by having a high intellectual intelligence (IQ), but to be wise, one must have spiritual intelligence (SQ). SQ will provide the ability to distinguish, moral intelligence, the ability to adjust rigid rules, understanding, and equal ability to understand the love of work and understand to the extent that it must be done.…”
Section: Introductionmentioning
confidence: 66%
“…In practice, emotional intelligence (EQ) and spiritual intelligence (SQ) must be carried out together by implementing Islamic leadership characteristics (EQ and SQ) so employee morale and employee performance can be realized. Previous research, such as (Ogunsola et al, 2020), found that emotional intelligence can increase the average performance of salespeople. Emotional intelligence can be applied in standard management concepts and affects employee performance or only understanding that can be trained at the level of personal ability.…”
Section: Introductionmentioning
confidence: 94%
“…Employees act out emotions that are required by the organization or conform to the demanding situation (Ogunsola, Fontaine & Jan, 2020). They portray positive emotions but they do not feel them, such as faking a smile (Lu, Wu, Mei, Zhao, Zhou, Li & Pan, 2019).…”
Section: Introductionmentioning
confidence: 99%